Reality of implementing educational justic in social affairs department- Benghazi branch, from employees’ perspective: A case study on social affair department-Benghazi branch - محمد العبار بشير; خليل الطيرة خالد (Dirasat in Economics and Business, 2024)
This study attempts to identify the reality of applying organizational justice (distribution justice, procedures justice, and transactions) from the perspective social affairs department employees in Benghazi. For the study purposes, the researchers adopted case study method. They also utilized a questionnaire as a tool of gathering data. The study population consisted of the staff of social affairs department within Benghazi city (58 subjects). They conducted the whole study by comprehensive confinement technique and used SPSS software to analyze the data. The main concluded results were that the level of the organizational justice with its collective dimensions (distribution justice, procedures justice, and transactions justice) was high. In addition, the level of applying these dimensions individually was high. The study did not find any significant differences in implementing the organizational justice in social affair department in Benghazi that can be attributed to gender variable. However, there were significant differences in implementation in terms of age and education level. Therefore, the researchers submitted some recommendations that may contribute in enhancement of the reality of applying the organizational justice in social affair department in Benghazi city.